The Perception of Students Toward Civic Learning to Improve the Quality of Learning Colleges in UPN “Veteran” Jawa Timur - S.I. Hidayat; L. F. L. Pratiwi; L. Diana (Future Science)
Civic education is a subject which consists of nationality education, democracy, civic and nationality law, for students to support the attainment of citizens who are aware of the rights and obligations, smart, skilled and reliable, so reliable to build a nation and a state based on Pancasila and the Constitution of the Republic of Indonesia of 1945 according to academic field and profession. This research aims to identify the perceptions of students who take civic education subject towards the material, lecturer, methods, and means of supporting learning. The methods used in this research is quantitative descriptive. Research location is selected by purposive sampling i.e. Universitas Pembangunan Nasional Veteran Jawa Timur because it is one of the campuses which has a vision of State Defense. The respondents of the research are students who have taken civic education subject. Respondents were selected by random sampling as many as 150 students. The results as obtained are that students have good perception towards the material, lecturer, and means of supporting learning while learning methods have worse perception because the method is considered less attractive. Learning methods should be repaired in order to make better perception so that students can contribute to the realization of Universitas Pembangunan Nasional Veteran Jawa Timur as a campus of the State's defense.